RNA sequencing for global gene expression associated with muscle growth in a single male modern broiler line compared to a foundational Barred Plymouth Rock chicken line. (December 2017) - Kong, Byung-Whi; Hudson, Nicholas; Seo, Dongwon; Lee, Seok; Khatri, Bhuwan; Lassiter, Kentu; Cook, Devin; Piekarski, Alissa; Dridi, Sami; Anthony, Nicholas; Bottje, Walter
Abstract Background Modern broiler chickens exhibit very rapid growth and high feed efficiency compared to unselected chicken breeds. The improved production efficiency in modern broiler chickens was achieved by the intensive genetic selection for meat production. This study was designed to investigate the genetic alterations accumulated in modern broiler breeder lines during selective breeding conducted over several decades. Methods To identify genes important in determining muscle growth and feed efficiency in broilers, RNA sequencing (RNAseq) was conducted with breast muscle in modern pedigree male (PeM) broilers (n = 6 per group), and with an unselected foundation broiler line (Barred Plymouth Rock; BPR). The RNAseq analysis was carried out using Ilumina Hiseq (2 x 100 bp paired end read) and raw reads were assembled with thegalgal4 reference chicken genome. With normalized RPM values, genes showing >10 average read counts were chosen and genes showing <0.05 p-value and >1.3 fold change were considered as differentially expressed (DE) between PeM and BPR. DE genes were subjected to Ingenuity Pathway Analysis (IPA) for bioinformatic functional interpretation. Results The results indicate that 2, 464 DE genes were identified in the comparison between PeM and BPR. Interestingly, the expression of genes encoding mitochondrial proteins in chicken are significantly biased towards the BPR group, suggesting a lowered mitochondrial content in PeM chicken muscles compared to BPR chicken. This result is inconsistent with more slow muscle fibers bearing a lower mitochondrial content in the PeM. The molecular, cellular and physiological functions of DE genes in the comparison between PeM and BPR include organismal injury, carbohydrate metabolism, cell growth/proliferation, and skeletal muscle system development, indicating that cellular mechanisms in modern broiler lines are tightly associated with rapid growth and differential muscle fiber contents compared to the unselected BPR line. Particularly, PDGF (platelet derived growth factor) signaling and NFE2L2 (nuclear factor, erythroid 2-like 2; also known as NRF2) mediated oxidative stress response pathways appear to be activated in modern broiler compared to the foundational BPR line. Upstream and network analyses revealed that the MSTN (myostatin) –FST (follistatin) interactions and inhibition of AR (androgen receptor) were predicted to be effective regulatory factors for DE genes in modern broiler line. PRKAG3 (protein kinase, AMP-activated, gamma 3 non-catalytic subunit) and LIPE (lipase E) are predicted as core regulatory factors for myogenic development, nutrient and lipid metabolism. Conclusion The highly upregulated genes in PeM may represent phenotypes of subclinical myopathy commonly observed in the commercial broiler breast tissue, that can lead to muscle hardening, named as woody breast. By investigating global gene expression in a highly selected pedigree broiler line and a foundational breed (Barred Plymouth Rock), the results provide insight into cellular mechanisms that regulate muscle growth, fiber composition and feed efficiency.